About non-knowledge in Knowledge management for planning: Towards an applied ontological approach - Stufano Melone, Maria Rosaria; Camarda, Domenico (TeMA - Journal of Land Use, Mobility and Environment, 2022)
This work contains reflections on the awareness of how the lack of knowledge and the unknown are important elements to consider during any territorial and environmental planning process. The unknown can affect dramatically the effectiveness of choices and start a chain of unpredictable consequences. The awareness of such issues emerged dramatically with the recent pandemic. Plans often deal with policy decisions, planning decisions that interest collectivity, human and non-human beings, our space, our territories and our time (or portions of time). Such plans (either for households or a city or a region) have to cope with unexpected events, uncertainties, with unwanted consequences. After an exploration of some theoretical aspects of knowledge and non-knowledge, we argue about the extent to which ontologies can be a useful conceptual approach to deal with the lack of knowledge and the unknown in planning.